Optic nerve regeneration. (December 2012) - Butt, Gibran Farook; Habib, Abubakar; Mahgoub, Kareem; Sofela, Agbolahan; Tilley, Mark; Guo, Li; Cordeiro, M Francesca
Optic nerve injury is a consequence of numerous ophthalmic conditions including glaucoma, a leading cause of global blindness. In adult humans, the optic nerve displays limited regenerative capacity, typical of neurons of the CNS. In efforts to address this issue, a number of recent advances have been made in the identification of potential therapeutic targets that directly inhibit or stimulate optic nerve regeneration, with more work implicating several other factors. These factors can be categorized as being intracellular or extracellular with respect to the neuron, or inflammatory cell-derived. In addition to these therapeutic strategies, it is important to guide the regrowing axons to their correct destination. Recent work has identified several developmental guidance factors important in regeneration, and potential therapeutic targets for the future. This review discusses newly identified and existing regeneration factors and evaluates current cellular- and nanotechnology-based therapies that aim to aid and guide optic nerve regeneration to achieve functional recovery.